Toxic Relationship In Movie Script Enough by Nicholas Kazan - Tandililing, Maida; Moelier, Dahlia D.; Asyrafunnisa, Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2025)
The study aimed to find out types of toxic relationship and to describe the effects of toxic relationship in the movie script entitled Enough. The researcher did some ways to succeed in doing the research. Firstly, reading the script to understand the story, and secondly, collecting some written text from the script to find out the data.  The researcher then applied descriptive qualitative method to describe the toxic relationship of the movie script. To achieve the aim, the theory of Toxic Relationship from Morgan Lee was functioned.  The results of the study showed that there were some toxic relationships described in the movie script.  From 19 data there were 4 types of toxic relationship, namely controller found in 5 data,  5 data of belittler deflector and 5 data of overreactor, and with 4 data of user's and possessive nature. It was also found  12 data of 4 effects of toxic relationship, each namely feeling angry sad and down 4 data, with 2 data of feel numb and sad, 2 data of unable to express yourself and there were also 4 data categorized as they control of the relationship.